Implementasi Guru Dalam Merancang Butir Kognitif Di MTS An-Najiyyah - duwi farihan ma'rifah; dita ramadhani; eka putri febrilia; evi nurdianti; fahrudin ashari; fatkhur rohman; Nurul Malika (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
The item questions are a crucial element in the educational assessment process, serving to measure students' understanding and thinking abilities. The design of test items is carried out by considering cognitive aspects in accordance with Bloom's Taxonomy, which encompasses various levels of thinking from basic knowledge to analysis and evaluation. This study employs a qualitative approach using interviews and observations to identify the steps taken by teachers in designing test items. The findings indicate that the teachers at MTs An-Najiyyah have made efforts to align the test items with the curriculum and learning outcomes, as well as to establish clear learning objectives as the foundation for designing the questions. However, challenges arise when teachers struggle to understand and identify each cognitive level, which can hinder their ability to formulate questions that align with the desired levels of thinking, particularly in creating questions that demand higher-order thinking skills (HOTS).